Effects of Climate and Land Use Change on Food Security: a Case Study of Phra Nakhon Si Ayutthaya Province, Thailand (European Journal of Formal Sciences and Engineering, 2019)
Addressing climate change for food security poses a great challenge to social welfare in developing countries where agricultural sector plays a significant role in driving economic growth and sustaining livelihoods. Natural climate variability and anthropogenic emissions introduce the considerable effects on agriculture yields and productivity, including nexus of food-water-energy. This paper aims at exploring land suitability for rice farmland in Phra NaKhon Si Ayuttaya province. Projection of temperature and precipitation over a province in 2050 in according to representative concentration pathway (RCP) 4.5 and 8.5 scenarios show a few increase in mean monthly temperature, monthly maximum temperature and minimum temperature about 0.5 to 1 degree celcius. Annual precipitation tends to be reduced for RCP 8.5 in comparison to RCP 4.5. Land suitability for growing rice is simulated by using EcoCrop model which requires input parameters from temperature and precipitation projection in 2050. Results reveal a decreasing in land suitability for rice both under RCP 4.5 and 8.5 scenarios. Agricultural land use tends to be transformed into residential and industrial land by 2050, resulting in the reduction in agricultural land and rice production. Successful adaptation to climate change in the agricultural sector needs to be encouraged by government to build robust cooperative efforts from all stakeholders.Keywords: Climate change; rice; Phra Nakhon Si Ayuttaya, food security; adaptation
Keywords: Climate change; rice; Phra Nakhon Si Ayuttaya, food security; adaptation